National identity of secondary school students in the Republic of Serbia - Ранђеловић, Душан Ј.; Минић, Јелена; Ранђеловић, Кристина (Sociološki pregled, 2021)
This paper was aimed at examining the structure and expression of national identity among secondary school students (N=568) in different towns in Serbia, its relation to self-esteem and achievement motive, as well as the differences regarding socio-demographic characteristics (sex and place of residence). The instruments used are the Scale of National Identity NAIT, the Global Self-Esteem Scale, and the Scale to Measure Achievement Motive MOP2002. The results have shown that the values of national identity are above the theoretical average and significantly higher than the values recorded among the adolescents in an earlier study. Among general characteristics of their own nation, secondary school students value culture more than history, character traits and state institutions (lowest-ranked in comparison to all other characteristics), finding that courage is the most pronounced individual characteristic, while the least pronounced one is hypocrisy. A positive correlation of national identity with self-esteem and achievement motive was obtained, whereas achievement motive is also a significant national identity predictor. Significant differences were found in the expression of national identity among secondary school students in relation to their place of residence (secondary school students from Belgrade have a higher level of national identity in comparison to their peers from Niš and Kosovska Mitrovica).
Keywords: national identity; self-esteem; achievement motive; secondary school students